Sistem Informasi Geografis Pemetaan Penyaluran Dana Bantuan Operasional (Studi Kasus di SMA Negeri Kota Pematangsiantar) - Hutagalung, Juniar (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2018)
Education is an important aspect for the progress of a country. With the existence of School Operational Assistance (BOS) funds can help the distribution of education but the Education Office has not implemented a computerized system to the maximum in monitoring the distribution of BOS funds. The Education Office only has data textually and not spatially. The more schools in Pematangsiantar City will be difficult for the Education Office to see a map of locations where schools that are entitled to receive BOS funds and who have received BOS funds. This Geographic Information System (GIS) application was made to find out the location of BOS funds distribution with the appearance of tables and data in the form of maps. This GIS is displayed web-based so that everyone can access it. The use of this application will help the Education Office in monitoring the distribution of BOS funds so that evenly distribution. In addition to helping the community to find out the location of the school and school data. The author uses google maps to determine latitude and longitude coordinate points found on google maps. Using this coordinate point, the location of the recipient of BOS funds was obtained. Latitude and longitude values are stored in the MySQL database and will be called using PHP programming. This application also uses UML modeling. This study uses data collection methods by means of surveys and literature. After the data has been collected, the location measurements and map determination are then analyzed for system requirements and system design and testing. Then the implementation of the system by utilizing Google Map and the PHP programming language. After the application is generated, the program is tested with Black Box Testing. This GIS application can run locally using a local server such as App Server with the provision that you must connect to the internet.